Cécile Mainardi's "Sorties": Poetry as Desire and Performance - Pradeau, Léon (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2024)
Cécile Mainardi is part of a generation of French poets who have been attempting, in the 1990s and 2000s, to activate their books in new ways—at galleries, art festivals, and performed readings. Though they are inscribed in the lineage of sound poetry and action poetry, these writers remain attached to the book, even if that medium is to be transcended. This article focuses on this tension by reading Mainardi’s poetic work through the lens of its desire to (be) perform(ed). The concept of “sorties,” borrowed from Jean-Marie Gleize (Sorties, 2009), helps explore the ways Mainardi articulates her relationship to poetry: at once a written form, and the expression of a desire to become someone or something else. She invites her readers to wonder what it means to read a poem that never ceases to announce or prefigure its performance: we stay with this tension between the text and its enactment. Mainardi’s poetry seems to involve its readers in a way that both engages their ability to imagine the poem as a performance, and asks them to become the poet’s partner, in a potentially erotic way. By drawing on the links between poetry and performance, this article investigates how poems might exceed the page and relate to their reader.